PRODUKSI DAN FORMULASI BIOINSEKTISIDA DARI PROPAGUL AKTIF JAMUR BEAUVERIA BASSANIA - Untung Suwahyono (Jurnal Teknologi Lingkungan, 2008)
Beauveria bassiana is a well known entomopathogenic fungus that has been widely used for biocontrol of many economically important pest of crops. Production technology for massive production of bioinsecticide B. bassiana still using liquid fermentation. Product formulation is the critical stage for producing bioinsecticide B. bassiana, since its success indicator is the contain of viable propagules in the final product after long period of storage. The aim of this study is to assess the optimal production of biomass and formulation of bioinsecticide B. bassiana. Result showed that the best production technology of bioinsecticide B. bassiana is by liquid fermentation, as an innovative method aimed to reduce the production cost. Assessment of formulation of bioinsecticide B. bassiana showed that formulation using simple raw materials to make a pasta without filler is the best choice to be further developed.